Voltage sags mitigation technique using PSCAD/EMTDC / Mohd Norhalim Safe - Safe, Mohd Norhalim (2010)
For some decades, power quality did not cause any problem, because it had no effect on most of the loads connected to the electric distribution system. When an induction motor is subjected to voltage sag, the motor still operates but with a lower output until the sag ends. With the increased use of sophisticated electronics, high efficiency variable speed drive, and power electronic controller, power quality has become an increasing concern to utilities and customers. Voltage sags is the most common type of power quality disturbance in the distribution system. It can be caused by fault in the electrical network or by the starting of a large induction motor. This project intends to investigate mitigation technique that is suitable for different type of voltage sags source with different type of loads. The simulation will be using PSCAD/EMTDC software. The mitigation techniques that will be studied are Dynamic Voltage Restorer (DVR), Distribution Static Compensator (DSTATCOM) and Solid State Transfer Switch (SSTS). All the mitigation techniques will be tested on different type of faults. The analysis will focus on the effectiveness of these techniques in mitigating the voltage sags. The study will also investigate the effects of using the techniques to voltage sag magnitude. At the end of the project it is expected that a few suggestions can be made on the suitability of the techniques.